A Study on the Design Criteria of Rapid Conversion into Infectious Disease Isolation Ward by Remodeling Type - Lee, Hyun Jin; Kwon, Soon Jung (Journal of the Architectural Institute of Korea, 2023)
This study aims to outline essential elements for the architectural design of a negative pressure isolation ward, facilitating swift responses to new infectious diseases and rapid adaptability. Three hospitals with operational rapid treatment isolation wards were visited for qualitative research conducted through focus group interviews. While the initial focus during the early stages of COVID-19 was on safety and functionality, future planning must consider design standards that prioritize urgency and adaptability for potential new infectious diseases. Ensuring the safety of medical staff involves three crucial steps during installation in the vestibule between the negative pressure area and the general area. In cases where installing an anteroom is challenging during hospital remodeling, a negative pressure hallway anteroom becomes mandatory. To streamline the movement of medical staff entering the general area without showering, and for efficient construction, minimizing the relocation of hospital room walls is recommended.
Keywords: Infectious Disease; Isolation Ward; Rapid Conversion; Remodeling